The Effect of Cinnamomum Leaves (Cinnamomum burmanni) Supplementation at Different Dosages on Growth and Survival Rate of Tilapia (Oreochromis niloticus) - Rahmawati, Firma Fika; Ubaidillah, Mohammad Fikri (Indonesian Aquaculture Society (MAI), 2017)
This trial was aimed to evaluate the effect different dossage of cinnamomum leaves (Cinnamomum burmanni) supplementation on the growth performance and survival rate of tilapia (Oreochromis niloticus). A 30-day feeding trial was conducted in 12 aquaria with water system. Ten fish with average body weight of 100 g were reared in 60 x 35 x 30 cm3 of aquarium. Fish were randomly selected and stocked in each aquarium. The experiment was designed according to completely random design with three treatments and three replicates in each treatment. Experimental diets were prepared as dry pellet with Cinnamomum burmanni leaves of 0,25%, 0,5%,1,0% respectively, for 30 days. Fish were fed with experimental diets three times daily at satiation level. Result of the experiment showed that addition of 0,25%, 0,5%, 1,0% cinnamomum leaves (Cinnamomum burmanni) gave spesific growth rate (SGR) 2,55±0,34%a, 2.15±0.25%b and 2.21 ± 0.16%a respectively; feed conversion ratio (FCR) 1,29±0,24a, 1,68±0,07%b, and 1,50±0,18%a respectively and survival rate (SR) all treatment were 100± 0,00%. If compared to control (SGR 1.87 ± 0.22%a, FCR 1.83±0.15%a and SR 100± 0,00%a), it was concluded that cinnamomum leaves dietary gave a better result, especially the addition of 0,25% cinnamomum leaves gave a significant increase of growth and feed convertion of tilapia (Oreochromis niloticus).